Risk Evaluation Indicator System for Lightning Disaster in Oil Storage Depots. Issue 1 (September 2021) - Liu, Kuirong; Wu, Dongrong; Xia, Ji; Chen, Wenqing; Chen, Ge; Liu, Jiayue; Li, Haocen
Abstract: Since oil storage depots typically hold large quantities of oil or gas, they are prone to the build-up of high energy and density levels. This paper established a lightning disaster risk assessment index system for oil storage depots that considered the primary causes for accidental explosions due to lightning and included four first-level, 13 second-level, and 13 third-level indexes. Furthermore, this index system was based on the analysis of the mechanism underlying lightning-causing accidents in different types of storage tanks. Furthermore, it involved the establishment principle for the comprehensive evaluation indicator system, denoting a "comprehensive system, distinct layering, and simplicity." This system includes four first-level evaluation index, 13 second-level evaluation index and 13 third-level evaluation index. It visualizes the affiliation relationship between different risks that may cause lightning accidents in oil storage depots, introduces the method used to obtain each underlying risk indicator and lays a theoretical foundation for assessing the lightning disaster risk in oil storage depots.